A Comparison Study in Partial Replacement of Coarse Aggregate with Coconut Shell in Concrete - Uzni, Nur Khairiyah; Hanapi, Nur Amalina (Recent Trends in Civil Engineering and Built Environment, 2021)
Demanding for natural resources in construction are increase and caused the resources to deplete and this paper studies about the coconut shell substitution with coarse aggregate’s impact to the concrete. The main objective is to investigate the percentage replacement of coconut shell’s influence to the work-ability and strength of the concrete by comparing two previous research. The methods of this study are review the previous research, collect the data from those research and lastly process and explain the data obtained.The coarse aggregate’s substitution with coconut shell caused the water absorption and water permeability to increase and compressive strength to decrease. Those stated are influenced by properties of coconut shell, cement, aggregate, admixtures, and process of treating the coconut shell. If future work are on comparison study, it is recommended to compare between the specimens with the same percentage replacement to get more accurate outcomes.